Description of two new species of the genus Pentacentrus Saussure from China (Orthoptera: Gryllidae) - Zong, Le; Qiu, Tengfei; Liu, Haoyu (Zootaxa, 2017)
The two new species of Pentacentrus Saussure 1878 are described and illustrated from China, P. medogensis sp. nov. and P. sororius sp. nov. Pentacentrus birmanus Chopard, 1969 is excluded from Chinese fauna.